The Models of Human Resource Development in Preparing Prisoners for Entrepreneurship in Banjarmasin - Zainal Arifin; Akhmad Yafiz Syam; Muhammad Maladi (Department of Management, Faculty of Economics and Business, Brawijaya University, 2013)
Tendency to ex-prisoners back into previous environment after being released from the detention center is a phenomenon that raises a big question. Although training programs have become routine activities provided by the government every year and inmates are trained in various skills in preparation for their after-free, some still choose to return to the criminal world. Empirical studies show that there are two main causes, namely (1) the training program is given to make them skilled workers that after they acquire freedom no company will hire former prisoners, (2) there are constraints such as capital and knowledge emerge as for those starting and running a business. A new approach is necessary for construction problems. This study attempts to test the model of human resource development for former prisoners to prepare them for entrepreneurship. This study is the first step in testing the model of development of human resources for ex-prisoners to prepare them for entrepreneurship. In this study, the object to be examined is inmates of a prison in Banjarmasin. The data collection is done by filling in questionnaires, in-depth interviews to 150 inmates of their last year before the end of the period of detention, business confidence surveys, training and mentoring consultancy. The results from the test using MSC-T Miner questionnaire method showed 100 of the 150 prisoners have entrepreneurial potential. 100 people have been matched with their preferred business qualifications only 50 people who have interest in accordance with market rates. Intervention by the research team is to provide motivation and knowledge about entrepreneurship and personality development showed better results than before the intervention of the 50 inmates in preparing for entrepreneurship.